iPads and the Use of “Apps” by Children with Autism Spectrum Disorder: Do They Promote Learning? - Allen, Melissa L.; Hartley, Calum; Cain, Kate (Frontiers in Psychology, 2016)
The advent of electronic tablets, such as Apple’s iPad, has opened up the field of learning via technology, and the use of electronic applications (‘apps’) on these devices continues to dramatically rise. Children with communication and social impairment, specifically those with Autism Spectrum Disorder (ASD), often use educational and recreational apps within the context of their home and school settings. Here we examine in which contexts learning via this medium may be beneficial, and outline recommendations for the use of electronic tablets and the design features for apps to promote learning in this population that is characterized by a unique profile of needs and heterogeneous ability levels.